Exploring the Interplay of Beauty: Shelley's and Dickinson's Poems through Mead's Theoretical Framework - Jesudas, Roseline (Journal Corner of Education, Linguistics, and Literature, 2024)
This study uses a symbolic interaction approach, specifically based on George Herbert Mead's ideas, to examine how Percy Bysshe Shelley's "Hymn to Intellectual Beauty" and Emily Dickinson's poem, “I died for beauty—but was scarce,” connect on certain themes. Using a qualitative approach that combines analysing the texts with considering the poets' social backgrounds, this research delves into how the poets express their views on beauty, truth, and mortality through symbolic interactions. This study shows that Shelley and Dickinson use beauty to explore deep questions about existence, reflecting their personal challenges and connections to society. The results of the study suggest that both poets go beyond just liking beauty; they use it as a platform for deep philosophical and emotional discussions that align with Mead’s ideas about the self and society. This analysis helps the readers see how symbolic interactions in poetry influence our experiences and cultural interpretations, shedding light on why these works are still important in today's conversations about beauty and identity.